PENGGUNAAN NATRIUM BIKARBONAT DALAM PEMBUATAN MINUMAN KARBONASI SARI BUAH NANAS DAN SEMANGKA - Sarifah Nur’aini; Shanti Fitriani; Yusmarini Yusmarini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
1. Mahasiswa Fakultas Pertanian Universitas Riau2. Dosen Fakultas Pertanian Universitas RiauJOM FAPERTA Vol. 7 Edisi 2 Juli s/d Desember The purpose of this research was to obtain the best formulation of sodium bicarbonate on chemical and organoleptic properties. This study used a complete randomized design with four replications, resulting in 16 experimental units. The treatment research were KSN1 (sodium bicarbonate 0.2%). KSN2 (sodium bicarbonate 0.4%), KSN3 (sodium bicarbonate 0.6%), and KSN4 (sodium bicarbonate 0.8%). Data obtained were statistically analyzed using analysis of variance and continued with duncan’s new multiple range test (DNMRT) at a 5% level. Parameters observed in this study included solubility of  gas, degree of acidity (pH), total acid, total dissolved solids, and sensory assessment (score test of carbonated drink and hedonic of taste). The result of this research showed that the concentration of sodium bicarbonate significantly affected solubility of  gas, degree of acidity (pH), total acid, and hedonic taste. The best treatment in this research was the concentration of KSN1 (sodium bicarbonate 0.2%) where moisture content solubility of  gas. 146.02 mg/l, degree of acidity (pH) 4.37, total acid 0.56%, total dissolved solids 23.87 ᴼBrix. Descriptive sensory assessment, namely the score of carbonation effect did not bite on the tongue and the overall assessment was favored by the panelists.Keywords: carbonated drinks, sodium bicarbonate, pineapple and watermelon